Tailored Coumarin Dyes for Photoredox Catalysis: Calculation, Synthesis, and Electronic Properties. Issue 3 (26th November 2020) - Gualandi, Andrea; Nenov, Artur; Marchini, Marianna; Rodeghiero, Giacomo; Conti, Irene; Paltanin, Ettore; Balletti, Matteo; Ceroni, Paola; Garavelli, Marco; Cozzi, Pier Giorgio
Abstract: High level time‐dependent density functional theory (TD‐DFT) computational modeling of coumarin dyes has been exploited for guiding the design of effective photocatalysts (PCs). A library of coumarins were investigated from the theoretical point of view and photophysical/electrochemical properties (absorption and emission spectra, E00, oxidation and reduction potentials) were evaluated. Comparison with literature values reported for a few candidates has been used for assessing the level of theory. On the basis of the results obtained, new strongly reducing PCs [ Eox (PC .+ /PC*)=−2.1 – −2.0 V vs SCE] were discovered. Through the computational study of structure‐properties relationships, a number of coumarins derivatives have been synthesized and evaluated in the pinacol coupling of aldehydes as the model reaction. The new organic photoredox catalysts show experimental photophysical and electrochemical data in accordance with the ones predicted by calculation, with excited state reduction potentials surpassing those of highly reducing transition metal‐based PCs. A careful investigation of their behavior as PC has revealed crucial issues that need to be taken into consideration in the general photoredox catalysis, shedding light on the use of these PC in the pinacol, as well as, in other photoredox reactions. Abstract : "Calculemus"! A theoretical and experimental approach was used to design new effective and performant coumarin organic dyes by combining calculations, simple and applicable synthetic methodology for an efficient design. Electrochemical and photophysical investigations confirmed the theoretical predictions.